Pantang Larang pada Kegiatan Ekonomi Puak Melayu Akit Hatas Pulau Rupat - Suci Nadia; Nursyirwan Effendi; Yevita Nurti (Anthropos: Jurnal Antropologi Sosial dan Budaya (Journal of Social and Cultural Anthropology), 2021)
The oral tradition is one of the traditions that can still be found in Old Malay Puak. For example, Gurindam, Koba, Rindai and so on. One of the oral traditions in Puak Melayu Akit Hatas Pulau Rupat is the tradition of Prohibition. Parents used to use the expression forbidden to forbid their children and grandchildren in teaching them how to behave so as not to harm themselves and others. The expression of prohibition varies, however the discussion of prohibition in this paper revolves around the variety, content and meaning of prohibition in community economic activities, including activities in the fields and at sea. Prohibition Usually is associated with unseen nature, natural disasters or animals which, if violated intentionally or not, will cause undesirable things. The number of shifts in cultural values due to the entry of new people around Puak Melayu Akit Hatas does not affect the public's view of the oral tradition. This paper is intended to describe how the sound and meaning of prohibition and how it is used in several economic activities in society.